2010
DOI: 10.1021/co1000458
|View full text |Cite
|
Sign up to set email alerts
|

Facile Diversity-Oriented Synthesis of Novel Dipeptide Mimetic Compounds Containing Bioactive Molecular Skeletons under Microwave Irradiation

Abstract: The diversity-oriented synthesis of dipeptide mimetic compounds embedded with bioactive molecular skeletons have been successfully established via microwave-assisted reactions between various 4-arylidene-2-phenyloxazol-5(4H)-ones and a broad scope of amines including aliphatic, aromatic, and heteroaromatic ones. This synthetic approach has prominent features of short reaction time, high yields, operational simplicity, as well as widespread applications, leading to a facile and straightforward access to structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Finally, due to the biological importance of dipeptides, a preliminary derivation of compound 3aa was performed by its aminolysis with propylamine, which efficiently generated chiral dipeptide mimetic compound 11 in a quantitative yield of 99% and a retained enantioselectivity of 99:1 er (eq ). …”
Section: Resultsmentioning
confidence: 99%
“…Finally, due to the biological importance of dipeptides, a preliminary derivation of compound 3aa was performed by its aminolysis with propylamine, which efficiently generated chiral dipeptide mimetic compound 11 in a quantitative yield of 99% and a retained enantioselectivity of 99:1 er (eq ). …”
Section: Resultsmentioning
confidence: 99%
“…In medicinal chemistry, it is reported that the incorporation of two bioactive moieties into another unique and complex structure may provide good opportunities for obtaining improved or new bioactivities . Besides, structure-based design and diversity-oriented synthesis have proven to be powerful tools to access structurally complex and diverse molecules with potential bioactivity .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, anti‐retroviral drugs such as HIV‐1 NCp7 inhibitors , anti‐inflammatory, antipyretic, analgesic activities, treatment of atherosclerosis , inhibitors of hepatitis C , and inhibitors for targeted melanoma therapy are remarkable properties of these compounds. Amide group is prepared via different methods such as reaction between primary amine and acyl chloride , nucleophilic attack to isothiocyanate , one‐pot condensation of an aldehyde, acetyl chloride, an enolizable ketone and acetonitrile , condensation of carboxylic acids with amines in the presence of nanosized sulfated titania , and ring‐opening of azlactones with amines . Recently, primary amides were synthesized directly from primary alcohols and ammonia using manganese oxide based octahedral molecular sieve (OMS‐2) as a heterogeneous catalyst .…”
Section: Introductionmentioning
confidence: 99%